Beneficial Treatment Outcomes of Severe COVID-19 Patients Treated Entirely in Primary Care Settings With Dexamethasone Including Regimen—Case Series Report - Vukoja, Damir; Jurić, Andrea; Erkapić, Zdravka; Pejić, Tomislav; Zovko, Željko; Juričić, Josipa; Pejić, Jelena; Ćorluka, Matea (Frontiers in Pharmacology, 2021)
Even in 2021, coronavirus disease 2019 (COVID-19) remains a major global health concern, especially in developing countries. The burden of this disease, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which affects not only primary respiratory but also other organ systems, keeps rising as the pandemic continues. Primary health care centers are the first line where COVID-19 patients are managed and should be able to manage the vast majority of them successfully. In this paper, we present a case series and concept of beneficial management of even deteriorating and severe patients treated entirely in our primary health center. The management is based on well-timed and rational dexamethasone use, as well as on various other pharmacological and nonpharmacological treatments and interventions, and is supported by provided statistical data. According to the presented experience and positive outcomes achieved, it seems that even deteriorating and severe COVID-19 patients can be treated successfully to some extent or even completely in primary care settings. This kind of approach could be particularly beneficial in conditions of overload of higher-level health care institutions.